2019
DOI: 10.12659/ajcr.916001
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Systemic Lupus Erythematosus Presenting as Autoimmune Myelofibrosis

Abstract: Patient: Female, 20 Final Diagnosis: Systemic lupus erythematosus (SLE) Symptoms: Anemia • fatigue • weakness Medication: — Clinical Procedure: — Specialty: Rheumatology Objective: Rare co-existance of disease or pathology Background: Systemic lupus erythematosus (SLE) is characterized by multiorgan involvement and presence of autoantibodies. SLE has a broad range of presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Autoimmune myelofibrosis can be detected in systemic lupus erythematosus (SLE), rheumatoid arthritis, autoimmune hemolytic anemia and ITP (19). In SLE, autoantibodies, immune complexes, and cytokines, es- pecially transforming growth factor-β (TGF-β) along with TGF-β, platelet derived growth factor (PDGF), vascular endothelial growth factor (VEGF), IL-2, IL-8, IL-17 and interferon-γ (IFN-γ) have been shown to be effective in fibrogenesis and those cytokines were blamed in the etiopathogenesis of autoimmune myelofibrosis (19)(20)(21)(22). Depending on these factors, collagen is produced by fibroblast activation in the bone marrow (22).…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune myelofibrosis can be detected in systemic lupus erythematosus (SLE), rheumatoid arthritis, autoimmune hemolytic anemia and ITP (19). In SLE, autoantibodies, immune complexes, and cytokines, es- pecially transforming growth factor-β (TGF-β) along with TGF-β, platelet derived growth factor (PDGF), vascular endothelial growth factor (VEGF), IL-2, IL-8, IL-17 and interferon-γ (IFN-γ) have been shown to be effective in fibrogenesis and those cytokines were blamed in the etiopathogenesis of autoimmune myelofibrosis (19)(20)(21)(22). Depending on these factors, collagen is produced by fibroblast activation in the bone marrow (22).…”
Section: Discussionmentioning
confidence: 99%
“…1 However, SLE associated AIMF is vanishingly rare, with just 48 other cases and only 6 in males ever reported. [2][3][4] The combination of AIHA and AIMF was only reported once in a male with SLE and Coombs positive hemolytic anemia 5 . Diagnosis of AIMF and differentiating this disorder from primary myelofibrosis is difficult given the lack prior reports.…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review published in 2015, a thorough assessment of hematological involvement in SLE suggested that myelofibrosis is a definitive finding of SLE, albeit its rare occurrence [3]. Current reports in the literature on BM fibrosis in the context of SLE are usually presented as case reports or reviews of such case reports [10][11][12][13][14][15][16][17][18]. The occurrence of BM fibrosis in SLE patients has been explored merely in few studies [6][7][8][9]19].…”
Section: Clinical Medicine Hypothesismentioning
confidence: 99%
“…Paquette et al have coined the term AIMF [21]. As of the 1990s up until now, case reports or case-based reviews have predominantly been published in this field [10][11][12][13][14][15][16][17][18]24]. Just a small number of studies have investigated BM in SLE cases [6][7][8][9].…”
Section: The Perception That Sle-associated Aimf Is Rarementioning
confidence: 99%